Joyland - King, Stephen (London Titan Books, 2013)
Set in a small-town North Carolina amusement park in 1973, Joyland tells the story of the summer in which college student Devin Jones comes to work as a carny and confronts the legacy of a vicious murder, the fate of a dying child, and the ways both will change his life forever
Keywords: City and town life -- North Carolina -- Fiction; Amusement parks -- Fiction; College students -- Fiction; Cold cases (Criminal investigation) -- Fiction